COMPARISON OF THE EFFICIENCY AND SAFETY OF ALBENDAZOLE AND PRAZIQUANTEL IN THE TREATMENT OF CYSTICERCOSIS (Vietnam Journal of Community Medicine, 2022)
Two drugs recommended to treat cysticercosis (ATSL) are albendazole and praziquantel, however,there have been few studies comparing these two drugs in Vietnam. Objective: To compare theefficacy and safety of albendazole and praziquantel in the treatment of ATSL. Methods: 120 patientswith ATSL having similar clinical characteristics were grouped for treatment by albendazole orpraziquantel according to the guidelines of the Ministry of Health. The evaluation was done 6 monthsafter the treatment. Results: The clinically cure and improvement rates were 61.7% and 38.3%. OnMRI, the rates of complete, partial cure and inefficacy were 65%, 30.8% and 4.2% respectively.The treatment achieved a cure rate of 51.7%, an improvement rate of 44.2% and an inefficacy rateof 4.2%. Praziquantel was more efficacious than albendazole in clinical, MR imaging and outcome.The studied patients did not show any abnormalities in levels of urea or creatinine. The patientsreceiving praziquantel had an increase in GPT abnormalities only after the third course. The patientstaking albendazole had an increase in liver enzymes after all treatment courses. The rate of liverenzyme elevation was higher in the albendazole group than in the praziquantel group. Conclusion:Praziquantel is more effective and safer than albendazole in the treatment of ATSL.
Keywords: Cysticercosis, praziquantel, albendazole, efficacy, safety.